Problem-based learning textbook: Its effect on improving creative thinking skills - Annisah, Siti; Aryanti, Zusy; Wildaniati, Yunita; Wahyuni, Sri (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Mathematics textbooks that provide more descriptions of material and routine problems used so far cannot facilitate students in active learning activities. The lack of active students in learning activities causes creative thinking skills not to develop optimally. This paper aims to describe how problem-based learning textbooks can facilitate students in solving problems with different or varied solutions and even something new to foster creative thinking skills. This problem-based textbook has been developed and is one of the research products of IAIN Metro lecturers in 2021. This research is an experimental study consisting of experimental and control groups. Data collection techniques using tests and observations. The test data were analyzed using the mean difference test using the Mann-Whitney formula, while the observation data were analyzed using a descriptive qualitative approach. The findings of this study are constructive learning activities and open problems contained in problem-based learning textbooks significantly improve creative thinking skills. It is shown that the increase in creative thinking skills of students who study using problem-based learning textbooks is substantially higher than students who study using other textbooks. Thus, problem-based learning textbooks contribute to improving students' creative thinking skills.